2013
DOI: 10.1292/jvms.12-0201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Injection Site on the Pharmacokinetics of Cefquinome Following Intramuscular Injection in Piglets

Abstract: ABSTRACT. The aim of the present study was to investigate the influence of different injection sites, i.e., the neck area and thigh muscle, on the pharmacokinetics of cefquinome in piglets following intramuscular (i.m.) injection. Cross-bred (Landrace × Duroc × Yorkshire) piglets were administered the same dose of cefquinome (2 mg/kg body weight) via intravenous injection and intramuscular injection into the neck area or thigh. The mean maximum concentrations (C max ) of cefquinome following i.m. injection int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The diffusion of cefquinome in the body tissues of different animal species is very small. In this study, barely 0.32 L ⁄kg of V ss was obtained in black swans similar to 0.25 L/kg in piglets and 0.19 L/kg in pigs [ 21 , 22 ]. According to the CVMP report, an attenuated distribution of cefquinome to intracellular spaces was due to low fat solubility and that it acts as an organic acid with a low pKa of 2.51 or 2.91 [ 5 ].…”
Section: Discussionmentioning
confidence: 82%
“…The diffusion of cefquinome in the body tissues of different animal species is very small. In this study, barely 0.32 L ⁄kg of V ss was obtained in black swans similar to 0.25 L/kg in piglets and 0.19 L/kg in pigs [ 21 , 22 ]. According to the CVMP report, an attenuated distribution of cefquinome to intracellular spaces was due to low fat solubility and that it acts as an organic acid with a low pKa of 2.51 or 2.91 [ 5 ].…”
Section: Discussionmentioning
confidence: 82%
“…The bioavailability ( F ) and time to peak concentration ( t max ) of cefquinome following IM administration were 97.8% and 0.43 h, respectively, reflecting its almost complete and relatively rapid absorption. These values were compatible with the results previously reported ranging from 93.3% to 103% and 0.38 to 0.45 h in mice, piglets and ducks, respectively (Limbert et al ., ; Yuan et al ., ; Song et al ., ). Compared to IM administration bioavailability of 98%, similar full bioavailability (107%) following SC injection was obtained.…”
Section: Discussionmentioning
confidence: 97%
“…Generally, the V ss from various species animals existed at low values, which indicated that cefquinome probably distributed mainly in the plasma compartment. The clearance rate (Cl) of cefquinome in dog (0.49 L·kg/h) in this study was higher than 0.18–0.34 L·kg/h in piglets, sows, wild boars, sheep, goats, rabbits, ducks and chicken (Song et al ., ; Block et al ., ; Uney et al ., ; Errecalde et al ., ; Hwang et al ., ; Yuan et al ., ; Xie et al ., ). These limited distributions and low clearance rate of cefquinome in the various species could be attributed to low fat solubility, protein binding activity and its pKa values of 2.51–2.91 (Hwang et al ., ; Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 99%